2010
DOI: 10.1242/jeb.041137
|View full text |Cite
|
Sign up to set email alerts
|

Income breeding and temperature-induced plasticity in reproductive traits in lizards

Abstract: SUMMARYWe used the northern grass lizard Takydromus septentrionalis as a model animal to examine the energy allocation strategy and whether body temperature can affect maternal reproductive traits in lizards. We maintained adult females collected from the field soon after winter dormancy under three thermal conditions (24.0±1.0°C, 28.0±1.0°C and 32.0±1.0°C) throughout the subsequent reproductive season, and then recorded their energy intake, digestive efficiency, body size and mass changes, and reproductive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…a higher priority for energy allocation towards growth and maintenance rather than to reproduction (Luo et al, 2010). Additionally, the described results in P. picta males do not support the hypothesis that final structural size in reptiles is determined by energy availability for growth.…”
Section: Discussioncontrasting
confidence: 77%
“…a higher priority for energy allocation towards growth and maintenance rather than to reproduction (Luo et al, 2010). Additionally, the described results in P. picta males do not support the hypothesis that final structural size in reptiles is determined by energy availability for growth.…”
Section: Discussioncontrasting
confidence: 77%
“…Among lizards, a similar pattern was reported in comparative studies of the genus Sceloporus (Angilletta et al, 2006). By contrast, grass lizards (Takydromus septentrionalis) produced the largest eggs at an intermediate temperature (Luo et al, 2010). This result might reflect differences between the life-histories of the grass lizard and the Madagascar ground gecko.…”
Section: Discussionsupporting
confidence: 72%
“…While this might indicate a difference in maternal investment, as there was no difference in RCM between experimental and control groups (Table1), we interpret these results as merely differences in allocation strategy (i.e. egg size versus number) possibly induced by experimental conditions (but see Luo et al, 2010). Another explanation for this result is that some factor, such as water content and hence egg mass, differed, but not maternal investment in yolk.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, higher temperatures, even if they only occur at night, are capable of causing an increase in annual reproductive output independent of growing season length. Although other studies have reported decreases in reproductive output above optimal temperatures due to physiologic stress (Luo et al, 2010), asymmetric climate warming could increase mean environmental temperatures without surpassing a species' thermal maximum as temperatures in the lower portion of the distribution rise disproportionately. Our data suggest that this would allow for an overall increase in clutch frequency and possibly subsequent survival among temperate ectotherms, a pattern reported previously (Bradshaw et al, 2004).…”
Section: Discussionmentioning
confidence: 85%